Regulation of learning: from the perspective of male students in Pakistan - Bakar, Z. A. (Nova Southeastern University, 2017)
Studies have shown that the students’ regulation of learning is associated to their learning outcomes, cognitive processing strategies and understanding of the content. In Pakistan, it was suggested that science students at secondary school possesses inadequate learning behaviours which diminished regulation of learning behaviours. This study was conducted with the intention to explore the issue of regulation of learning among secondary school science students in Pakistan. Twenty-four male students were selected purposefully to participate in the study. The data was collected through focus group interviews to understand their view of self-regulation of learning behaviour. The Applied Thematic Analysis was executed to analyse the student’s comments. It was found that the external regulation of learning in Pakistani secondary school science students were presence. Three common factors such as gender, teaching methods, and field of study were highlighted by the participants as a vital role in the development of external regulation of learning. The findings promote changes in teaching and learning approaches at the Pakistani secondary school level in science teaching.